Sensitivity of gyre-scale marine connectivity estimates to fine-scale circulation - Saeed Hariri; Sabrina Speich; Bruno Blanke; Marina Lévy (Ocean Science, 2023)
We investigated the connectivity properties of an idealized western boundary current system separating two ocean gyres, where the flow is characterized by a well-defined mean circulation as well as energetic fine-scale features (i.e., mesoscale and submesoscale currents). We used a time-evolving 3D flow field from a high-resolution (HR-3D) ocean model of this system. In order to evaluate the role of the fine scales in connectivity estimates, we computed Lagrangian trajectories in three different ways: using the HR-3D flow, using the same flow but filtered on a coarse-resolution grid (CR-3D), and using the surface layer flow only (HR-SL). We examined connectivity between the two gyres along the western boundary current and across it by using and comparing different metrics, such as minimum and averaged values of transit time between 16 key sites, arrival depths, and probability density functions of transit times. We find that when the fine-scale flow is resolved, the numerical particles connect pairs of sites faster (between 100 to 300 d) than when it is absent. This is particularly true for sites that are along and near the jets separating the two gyres. Moreover, the connectivity is facilitated when 3D instead of surface currents are resolved. Finally, our results emphasize that ocean connectivity is 3D and not 2D and that assessing connectivity properties using climatologies or low-resolution velocity fields yields strongly biased estimates.